Identificação de espermátides em testículo humano pelo método de sonicação para aplicação em reprodução assistida - Lilian Massara Martinelli (2016)
Azoospermia is an infertility condition characterized by the absence of spermatozoa in the ejaculate. In many cases, paternity can only be achieved by assisted reproduction, i.e. with testicular sperm extraction and subsequent intracytoplasmic spermatozoa injection (ICSI), a process known as in vitro fertilization. For spermatozoa extraction manual mechanical fragmentation of testicular parenchyma and search of spermatozoa under light microscope are frequently used with no complete success. However, it is unknown whether the fact of not having found sperm is by their absence in the testis or failure in the search method. This study evaluated the efficacy of sonication method of testicular fragments, employing dissociation of testicular tissue and degeneration of cells, with the exception of elongated spermatid heads, in order to determine more accurately the presence of this cell type in the testis of patients with azoospermia. Histopathological analysis of the testes showed that in all patients, the testes were similar, with typical hypospermatogenesis (Johnsen score ~ 8). The preservation of the spermatid heads after sonication using different combinations of frequency and time, was verified by the method of concentration of the sonication product by Cytospin followed by staining with the kit Panotic. The combination 60Hz/90s of sonication proved to be the best to keep the integrity of the heads of spermatids besides the elimination of other cell types. When carried out the prediction of sperm production from spermatid heads counting, it was found that there was no difference between the different combinations of frequency and time tested, regardless of the microscopy used for counting, fluorescence or phase-contrast. Thus, all combinations could be applied, however, taking in account the better preservation of isolated intact spermatid heads, attested by Cytospin method, we suggest the combination 60Hz / 90s to predict sperm production.